Genetic mapping of stripe rust resistance in a geographically diverse barley collection and selected biparental populations - Singh, Davinder; Ziems, Laura; Chettri, Mumta; Dracatos, Peter; Forrest, Kerrie; Bhavani, Sridhar; Singh, Ravi; Barnes, Charles W.; Zapata, Patricio Javier Noroña; Gangwar, Om; Kumar, Subodh; Bhardwaj, Subhash; et al. (Frontiers in Plant Science, 2024)
Barley stripe or yellow rust (BYR) caused by Puccinia striiformis f. sp. hordei (Psh) is a significant constraint to barley production. The disease is best controlled by genetic resistance, which is considered the most economical and sustainable component of integrated disease management. In this study, we assessed diversity of resistance to Psh in a panel of international barley genotypes (n = 266) under multiple disease environments (Ecuador, India, and Mexico) using genome wide association studies (GWAS). Four QTL (three on chromosome 1H and one on 7H) associated with resistance to Psh were identified. The QTL were validated by mapping resistance to Psh in five biparental populations, which detected key genomic regions on chromosomes 1H (populations Pompadour/Zhoungdamei, Pomapadour/Zug161, CI9214/Baudin), 3H (Ricardo/Gus) and 7H (Fumai8/Baronesse). QTL RpshQ.GWA.1H.1 detected by GWAS and RpshQ.Bau.1H detected using biparental mapping populations colocated, were the most consistent and stable across environments and are likely the same resistance region. RpshQ.Bau.1H was saturated using population CI9214/Baudin by enriching the target region, which placed the resistance locus between 7.9 and 8.1 Mbp (flanked by markers sun_B1H_03, 0.7 cM proximal to Rpsh_1H and sun_B1H_KASP_02, 3.2cM distal on 1HS) in the Morex reference genome v.2. A KASP marker sun_B1H_KASP_01 that cosegregated for RpshQ.Bau.1H was developed. The marker was validated on 50 Australian barley cultivars, showing well-defined allelic discrimination and presence in six genotypes (Baudin, Fathom, Flagship, Grout, Sakurastar and Shepherd). This marker can be used for reliable marker assisted selection and pyramiding of resistance to Psh, and in diversifying the genetic base of resistance to stripe rust.